Navigating foster care: how parental drug use and caregiver attitudes shape children’s mentalization processes—an exploratory longitudinal follow-up study: study protocol - Springer, Nadja; Lueger-Schuster, Brigitte (Frontiers in Psychology, 2024)
Background The current research concept of mentalization is used in the study to clearly identify affective and cognitive abilities of the caregiver-child dyad with the aim of compensating deficits on both sides with psychological-psychotherapeutic strategies. Methods The objective of this explorative, longitudinal intervention study is to provide an in-depth understanding of the psycho-social background of 30 children aged 6–12 years living in institutional or family-centered foster care. Data will be collected at three time points: before, after and 12 months after participating in the newly developed group intervention, which intends to address the particular needs of children of drug abusing parents living in foster care in the latency period. The study is conducted at the Faculty of Psychology of the University of Vienna in collaboration with the Association “Dialogue” (Verein Dialog). The treatment duration spans 5 months, during which two specifically trained psychotherapists conduct 10 group sessions for children and three group sessions for foster caregivers. All statistical analyses will consider the type of data available. Therefore, the primary outcome of the study will be assessed via the Friedman test due to the ordinal dependent variable as it is the non-parametric alternative to the one-way ANOVA for repeated measures. In addition, the Mann–Whitney U test is used to compare differences between two independent groups (children living in institutional foster care vs. family foster care). To assess potential correlations regarding the child and caregivers’ capacity to mentalize, Spearman correlations (ρ) are conducted. To examine the secondary outcome, apart from the methods previously outlined, we will also utilize qualitative thematic analysis. Discussion The present study uses the current research concept of mentalization to identify affective and cognitive abilities of the caregiver-child dyad with the aim of compensating deficits on both sides with psychological-psychotherapeutic strategies. There are some limitations of the study to mention: the small sample size does not allow to generalize the results. Due to the lack of a comparison group, a randomized control study (RCT) was not conducted. The authors are aware of these limitations. However, the studies’ findings, will help to deduce research questions for further studies.